Adaptive strategies employed by informatics teachers at SMAN 1 Parongpong within the context of Kurikulum Merdeka - Dinda Natania Sugara (Hipkin Journal of Educational Research, 2025)
In the ever-evolving digital era, Informatics has become crucial for equipping students with 21st-century skills, including computational thinking, problem-solving, collaboration, and digital literacy. This subject not only serves as an introduction to technology but also as a foundation for developing students' logical and innovative thinking. This study aims to identify and analyze adaptive strategies implemented by teachers in the Informatics learning process, adapted to the characteristics of the Kurikulum Merdeka. The need for adaptive strategies arises from various challenges still encountered in the field, such as the high complexity of teaching materials, limited technological facilities and infrastructure in schools, and the low readiness of teachers and students to adapt to curriculum changes. This study employed a descriptive qualitative approach, collecting data through semi-structured interviews and documentation of teaching materials. The results show that teachers at SMAN 1 Parongpong apply Problem-Based Learning and Project-Based Learning models, optimize the use of digital media such as learning videos and online applications, and develop flexible lesson plans and project-based assessments. These strategies not only increase student engagement and motivation to learn but also effectively and contextually support the achievement of the Kurikulum Merdeka objectives in Informatics subjects.   Abstrak Di era digital yang terus berkembang, Informatika menjadi aspek penting dalam membekali murid dengan keterampilan abad ke-21, seperti berpikir komputasional, pemecahan masalah, kolaborasi, dan literasi digital. Mata pelajaran ini tidak hanya berfungsi sebagai sarana pengenalan teknologi, tetapi juga sebagai landasan dalam membentuk pola pikir logis dan inovatif pada murid. Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis strategi adaptif yang diterapkan oleh guru dalam proses pembelajaran Informatika yang disesuaikan dengan karakteristik Kurikulum Merdeka. Kebutuhan akan strategi adaptif muncul karena masih ditemukannya berbagai tantangan di lapangan, seperti kompleksitas materi ajar yang tinggi, keterbatasan fasilitas dan infrastruktur teknologi di sekolah, serta rendahnya kesiapan guru dan murid dalam menghadapi perubahan kurikulum. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode pengumpulan data melalui wawancara semi-terstruktur dan studi dokumentasi perangkat ajar. Hasil penelitian menunjukkan bahwa guru di SMAN 1 Parongpong menerapkan model pembelajaran Problem-Based Learning dan Project-Based Learning, mengoptimalkan penggunaan media digital seperti video pembelajaran dan aplikasi daring, serta menyusun rencana pembelajaran fleksibel dan asesmen berbasis proyek. Strategi-strategi ini tidak hanya meningkatkan keterlibatan dan motivasi belajar murid, tetapi juga mendukung pencapaian tujuan Kurikulum Merdeka secara efektif dan kontekstual dalam mata pelajaran Informatika. Kata Kunci: Informatika; Kurikulum Merdeka; model pembelajaran; strategi pembelajaran